Konsep Tawasul dalam Al-Qur’an: Kajian Komparatif Tafsir Klasik dan Kontemporer - Yuni Fatonah (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2021)
This research discusses the concept of Tawasul in accordance with thearguments of the Qur'an and the Sunnah. In this study, the authors uses libraryresearch by collecting primary data such as from the Qur'an, hadith, as well as secondary source as tafsir at-Tabari, tafsir fi zilalil Qur'an, and tafsir al-Mishbah, as well as several books and theses related to the theme of tawasul. Furthemore, the verses about tawasul are studied and analyzed using the mothode of comparative interpretation of the opinions of classical and contemporart commentators. This Study indicates that the correct tawasul according to the arguments of al-Qur'an is to perform tawasul by being closer to Allah obediently and doing deeds that are pleasing to him, so that Allah erases our mistakes. In addition, there is also the concept of tawasul by asking permissionfreom Allah through wasilah righteous deeds that have been done while asking hopefully from Allah SWT.